The teaching of Afro-Brazilian and indigenous history and culture in the context of school geography: reflections on the implementation of law 11,645 / 2008 in the state public network of Pernambuco - Rosa, Wedmo Teixeira (Revista Ensino de Geografia (Recife), 2021)
The promulgation of Law 10,639/2003 and its subsequent expansion with Law 11,645/2008 constituted legal instruments that enabled Brazilian society to question the hegemonic school content and demand effective actions that decolonize school curricula. However, the effective implementation of this legislation in Brazilian basic education and in Pernambuco, in particular, is proceeding slowly. This work aims to discuss the main strategies developed by the State of Pernambuco for the effective implementation of Law 11.645/2008 in the schools of the state education network and to analyze its developments in the teaching of Geography. Based on a qualitative methodological approach, bibliographical and documentary research was carried out, in addition to semi-structured interviews with people relevant to the research (teachers, pedagogical coordinators and managers). It was found that despite the State of Pernambuco implementing a series of actions and strategies to contribute to the education of ethnic-racial relations, there are still serious problems in this process, especially in bringing educators and managers to the subject and makes it more present in school life. It was also found thatschool geography has gaps in the theoretical-methodological guidelines and teaching practices that deal with the theme of ethnic-racial relations.